Inovasi Frozen Food Patin, Qr Code Terintegrasi Aplikasi Camilan Cegah Stunting - Pridayanti, Anggie; Dahriansah, Dahriansah; Apridonal, Yori (STMIK Royal Kisaran, 2025)
Abstract: Stunting remains a significant chronic nutritional problem in Indonesia, with a prevalence of 21.6% in 2023. The primary cause is a lack of balanced nutritional intake from an early age. This research aims to develop an innovative healthy food product in the form of frozen food made from nutrient-rich catfish and moringa leaves, integrated with a QR Code system into the